Talcum Powder Toxicosis in Pregnancy - Jon F. Pennycuff; Abigail Davenport; Jane Ellis; Elizabeth Patberg; Carrie Cwiak (Thieme Medical Publishers, Inc., 2018)
Abstract Background Pica is a relatively common phenomenon in pregnancy and typically includes consumption of nontoxic substances such as earth/clay, raw starches, and ice. Occasionally, substances may be toxic or have unintended consequences. Case A nulliparous woman presented to our facility complaining of numerous, vague symptoms that are common in pregnancy. She had multiple work-ups and an admission to our antepartum unit without clear etiology of her symptoms. Ultimately, she was diagnosed with talcum powder toxicosis secondary to talc ingestion as a coping mechanism for her anxiety, which was heightened in pregnancy. Conclusion This case highlights the importance of screening for mental health disorders, which may be exacerbated during the peripartum period. Patients' coping mechanisms for mental health disorders may have unintended consequences.